2020
DOI: 10.3390/ijms21093274
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiling Reveals an Abundant miR-200a-3p Promotes Skeletal Muscle Satellite Cell Development by Targeting TGF-β2 and Regulating the TGF-β2/SMAD Signaling Pathway

Abstract: MicroRNAs (miRNAs) are evolutionarily conserved, small noncoding RNAs that play critical post-transcriptional regulatory roles in skeletal muscle development. Chicken is an optimal model to study skeletal muscle formation because its developmental anatomy is similar to that of mammals. In this study, we identified potential miRNAs in the breast muscle of broilers and layers at embryonic day 10 (E10), E13, E16, and E19. We detected 1836 miRNAs, 233 of which were differentially expressed between broilers and lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In the chicken, researches have shown that there are obvious phenotypic differences between FMGB and SMGL [ 4 , 18 ]. The underlying mechanism involves series of biological events, which contains many genes, signaling molecules and non-coding RNAs [ 20 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the chicken, researches have shown that there are obvious phenotypic differences between FMGB and SMGL [ 4 , 18 ]. The underlying mechanism involves series of biological events, which contains many genes, signaling molecules and non-coding RNAs [ 20 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that PDLIM3 plays important roles in maintaining muscle cell stability, cell differentiation, cell signal transduction, cell proliferation, and cytoskeletal structure integration and that it has a positive role in muscle development. In the research we have reported, RNA-Seq and RT-qPCR show that gga-miR-3525 is likely to play an inhibitory role in myogenesis [10]. Therefore, because of the mechanism of action of miRNA, we chose PDLIM3 as a target gene of gga-miR-3525 for subsequent verification.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing our previous miRNA-Seq and RNA-Seq data (NCBI accession number PRJNA516545), we found that gga-miR-3525 was differentially expressed in chickens with different muscle growth rates (p < 0.05, broilers and layers). Sequencing and real-time quantitative polymerase chain reaction (RT-qPCR) data showed that the expression of gga-miR-3525 in broilers (high growth rate) was lower than that in layers (low growth rate), suggesting that gga-miR-3525 may have a negative effect on skeletal muscle development [10]. gga-miR-3525 (miRBase accession number: MIMAT0016382) is specifically expressed in chickens [11]; it was first identified in the lungs and trachea of chickens infected with avian influenza virus and found to target the interleukin-6 signal converter (IL6ST) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Both play a role in skeletal muscle growth and development [ 24 ]. Domestic chicken skeletal muscle studies are primarily concerned with the construct of the miRNA library and the function of specific miRNAs across breeds (high vs. low selection broilers [ 25 , 26 ] large vs. small broilers [ 27 ], broilers vs. laying hens [ 28 ]), developmental stages (embryonic [ 29 ], postnatal [ 30 , 31 ], embryonic to postnatal [ 8 ]), and skeletal muscle tissues (pectoral muscles, leg muscles). They are involved in a variety of biological processes related to skeletal muscle development and play a crucial role via a complex regulatory network.…”
Section: Mirna Modulates Skeletal Muscle In Domestic Chickenmentioning
confidence: 99%
“…The expression of MiR-200a-3p was found to be upregulated at embryo stages E10, E13, E16, and E19 in broiler and laying hen pectoral muscles and was significantly higher in broilers than in laying hens. The functional validation in vitro demonstrated that it could target transforming growth factor 2 ( TGF-2 ) to regulate the TGF-2/SMAD signaling pathway, accelerating the differentiation and proliferation of chicken SMSCs and inhibiting apoptosis [ 28 ]. MiR-148a-3p downregulates the expression of mesenchymal homology frame 2 ( Meox2 ) and activates the PI3K/AKT signaling pathway to promote SMSC differentiation and inhibit apoptosis without affecting proliferation [ 49 ].…”
Section: Mirna Modulates Skeletal Muscle In Domestic Chickenmentioning
confidence: 99%